Substrate influence on aromatic plant growth in extensive green roofs in a Mediterranean climate - Monteiro, Cristina M. (2017)
Green roofs have been described as technical solutions to overcome urban environmental problems, such as decrease of vegetation and stormwater management. In the present study, two pilot 20 m2 extensive green roofs were implemented in an urban Mediterranean region, at a 1st storey on a warehouse building structure, in order to test the adequacy of different substrates for supporting aromatic plants (Lavandula dentata, Helichrysum italicum, Satureja montana, Thymus caespititius and Thymus pseudolanuginosus). Experimental substrates included expanded clay and granulated cork as main components, supplemented with organic matter and crushed egg shell. A commercial substrate that obeys to FLL guidelines was also tested. Plant growth was assessed and compared within each platform. All experimental substrates proved to be adequate for vegetation growth, with the combination of 70% expanded clay, 15% organic matter and 15% crushed egg shell showing the best results regarding plant establishment and growth over time. Water runoff quality parameters - turbidity, pH, conductivity, NH4+, NO3−, PO43− - met standard values required for water reuse for non-potable purposes, such as toilet flushing or irrigation. Preliminary qualitative thermographic measurements comparing surface temperature of different plant species and the substrate showed that temperature of vegetation surface was lower than substrate, reinforcing green roofs benefits of lowering air temperature in their surroundings. The present research shows that aromatic vegetation combined with clay substrates are suitable for green roofs located in countries of the Mediterranean region.